Idiomatic Expression Used in Malay Labuhanbatu Wedding Ceremony - Sisila Fitriany Damanik; Tiarnita Maria Sarjani Siregar (Britain International for Academic Research (BIAR) Publisher, 2019)
The aim of this study is to find out types of idiomatic expression in Malay Labuhanbatu Wedding Ceremony (MLWC). This study was conducted by applying descriptive qualitative research. The data were collected by applying documentary and interview technique, and applying the theory of Charles F Hockett to analyzed the types of idiomatic expression in MLWC. Charles F Hockett divides the types of idiomatic expression into 5 types, Proper Names, Abbreviation, English Phrasal Compounds, Figure of Speech and the theory of Abdul Chaer is used to analyzed the applying of Idiomatic expression in MLWC. After analyzing the data, it is found that Malay Labuhanbatu wedding ceremony are used to maintain the respect in the social relation of society, to preserve the Idiomatic Expresssion in Malay Labuhanbatu, and to enrich the Malay language, and the last to present the Malay Culture through the use of idiom